1975
DOI: 10.1111/j.1365-2141.1975.tb00547.x
|View full text |Cite
|
Sign up to set email alerts
|

The Endotoxin‐induced Coagulant Activity of Human Monocytes

Abstract: Leucocyte suspensions, exposed to endotoxin in vitro, develop coagulant activity which has been identified as tissue factor. Pure suspensions of polymorphonuclear (PMN) neutrophils, lymphocytes and monocytes were exposed to endotoxin and tested for tissue factor activity after 4 h incubation at 37 degrees C. The results indicate that the monocyte is the cell primarily responsible for the endotoxin-induced coagulant activity of mixed leucocyte suspensions, the small amount of activity demonstrated in PMN neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
0
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(167 citation statements)
references
References 8 publications
6
160
0
1
Order By: Relevance
“…Endotoxin can induce fibrin accumulation in vivo through the Shwartzman reaction (14), presumably by activating monocytes to express tissue factor (15). For this reason it is recognized as the component primarily responsible for blood coagulation associated with bacterial infections.…”
Section: S534 -S536) Our Results Indicate That Bacterial Proteimentioning
confidence: 99%
“…Endotoxin can induce fibrin accumulation in vivo through the Shwartzman reaction (14), presumably by activating monocytes to express tissue factor (15). For this reason it is recognized as the component primarily responsible for blood coagulation associated with bacterial infections.…”
Section: S534 -S536) Our Results Indicate That Bacterial Proteimentioning
confidence: 99%
“…After incubation with Gram-negative endotoxin in vitro, blood monocytes synthesize and express membrane tissue factor (TF), a potent initiator of the coagulation cascades [1]. Mononuclear cells from patients with meningococcemia also show TF activity, that correlates with the prognosis of the disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…During sepsis, bacterial mediators such as lipopolysaccharide (LPS) trigger the generation of microthrombi and the consumption of coagulation factors and their endogenous inhibitors, thereby leading to disseminated intravascular coagulation (DIC). 1,2 LPS stimulates endothelial cells 3 and blood monocytes 4,5 to express tissue factor (TF); TF then forms a highly procoagulant complex with activated factor VII (FVIIa), which initiates the coagulation cascade during endotoxemia. 6,7 Ongoing DIC causes changes in plasma levels of all coagulation factors: clinical studies reported decreased levels of FVIIa 8 and increased levels of soluble TF, 9 prothrombin fragment (F 1ϩ2 ), and soluble fibrin, resulting in increases of fibrin split products such as D-dimer.…”
mentioning
confidence: 99%